1986
DOI: 10.1038/clpt.1986.177
|View full text |Cite
|
Sign up to set email alerts
|

Human pharmacokinetics of the antiviral drug DHPG

Abstract: The pharmacokinetics of the antiviral drug 9-[2-hydroxy-1-(hydroxymethyl) ethoxymethyl]guanine (DHPG) were examined in six patients receiving 2.5 or 5.0 mg/kg every 8 or 12 hours for human cytomegalovirus (HCMV) pneumonitis or retinitis. Biexponential decay with a mean distribution t1/2 of 0.23 hours and terminal t1/2 of 2.53 hours was observed. Total clearance correlated well with and exceeded creatinine clearance by a factor of 2.4. Mean volume of the central compartment was 15.26 L/1.73 m2 and the volume of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
94
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(103 citation statements)
references
References 0 publications
9
94
0
Order By: Relevance
“…Low trough levels have been previously reported in a small study of paediatric transplant patients, with levels <0.5 mg/L being significantly more common in younger patients [12]. The observation that fewer babies <28 days had trough levels <0.5 mg/L compared with the overall age group <6 months would be in keeping with the almost exclusive renal excretion of GCV and the known immature renal function Peak levels were also in keeping with those reported in other clinical studies and were well above the MIC and IC 50 observed in vitro [6,7]. The relatively high frequency of peak levels <3.0 mg/L in younger age groups would, however, give rise to concerns regarding treatment failure, particularly if the disease-causing virus had an IC 50 at the upper range of those reported in vitro (3.48 mg/L).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Low trough levels have been previously reported in a small study of paediatric transplant patients, with levels <0.5 mg/L being significantly more common in younger patients [12]. The observation that fewer babies <28 days had trough levels <0.5 mg/L compared with the overall age group <6 months would be in keeping with the almost exclusive renal excretion of GCV and the known immature renal function Peak levels were also in keeping with those reported in other clinical studies and were well above the MIC and IC 50 observed in vitro [6,7]. The relatively high frequency of peak levels <3.0 mg/L in younger age groups would, however, give rise to concerns regarding treatment failure, particularly if the disease-causing virus had an IC 50 at the upper range of those reported in vitro (3.48 mg/L).…”
Section: Discussionsupporting
confidence: 77%
“…The therapeutic ranges often quoted in clinical studies were first derived from a study in five bone marrow transplant patients and one acquired immune deficiency virus (AIDS) patient with documented CMV retinitis or pneumonitis [7]. In that study, peak plasma concentrations ranged from 4.75 mg/L to 6.2 mg/L and trough concentrations from 0.25 mg/L to 0.63 mg/L.…”
Section: Page 4 Of 19mentioning
confidence: 99%
“…Unspecific toxicity, as shown by TK À cells, was minimal with the concentrations of GCV applied, which are within the plasma concentrations achievable in patients after intravenous infusion. 11,27 These data show that TK /GCV is effective in SH -EP neuroblastoma cells by affecting proliferation, metabolic cell survival, apoptosis, and clonogenicity.…”
Section: Resultsmentioning
confidence: 81%
“…Since D341Med-TK cells were killed by GCV treatment DNA synthesis, determined by standard 3 H-thymidine in vitro at concentrations usually reached in a clinical setincorporation assay, and cell growth, studied by MTT ting, 23 we assessed whether D341Med-TK cells were assay, were significantly higher in D341Med-tk cells sensitive to in vivo treatment, as well. Five mice were (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…These observations lead to reported for most brain tumor cell lines and which can be obtained in vivo. 23 Moreover, no toxicity was observed the speculation that the transfer of the connexin-43 gene into D341Med cells could increase the bystander effect, at the same GCV concentrations in untransfected D341Med cells. Some decline of cell viability was seen as previously demonstrated in the U87 glioma cell line.…”
Section: Figure 5 Connexin-43 Expression In D341med Cells Fifty Micrmentioning
confidence: 98%